(untitled) (Journal of the College of Basic Education, 2022)
This research starts from the assumption that anthropological linguistics is a distinct discipline that deserves to be studied for its past accomplishments as much as for the vision of the future presented in the work of a relatively small but active group of interdisciplinary researchers. Their contributions on the nature of language as a social tool and speaking as a cultural practice have established a domain of inquiry that makes new sense of past and current traditions in the humanities and the social sciences and invites everyone to rethink about the relationship between language and culture.